Analisis Tingkat Preferensi Pemilihan Moda Transportasi Antar Kota Antar Provinsi dengan Metode AHP Topsis (Study Kasus Rute Cilacap - Yogyakarta) - Prasetyo, Gandha Yugo; Muthohar, Imam; Malkhamah, Siti (Proceedings Series on Physical & Formal Sciences, 2021)
There are different characteristics between the modes of land transportation, such as trains, buses and cars from Cilacap to Yogyakarta, the Inter-City Inter-Provincial route. This gave a question of what criteria a person chose in determining the mode of transportation preferences. A questionnaire was required for data collection, determining the number of respondents (users). There were 20 respondents; 55% have low income, 10% have middle income, 35% have a high income. Then the data from filling out the questionnaire was analyzed using the AHP-TOPSIS method to determine the weight of the research criteria that had the most influence on preferences for transportation modes. With the results of the weighted criteria: safety (47.80%), comfort (19.78%), travel time (12.47%), frequency (12.12%) and cost (7.83%). Furthermore, the results of the preferences for the choice of transportation modes showed that the first rank was achieved by cars (0.73), secondly by buses (0.66) and thirdly by trains (0.58). The sensitivity test results showed that increasing the weight of the comfort criteria would reduce the priority of the bus mode. As for the training mode, it could be increased by adding weight to the cost criteria.